Tiga Faktor Dominan Penyebab Kegagalan Toilet Training pada Anak Usia 4-6 Tahun - Wiwik Agustina; Rendi Feri Sapta (STIKes Patria Husada Blitar, 2015)
Toilet training in children is an attempt to train children to be able to control in conduct urinating or defecating. There are many factors that might could affect toilet trainingÂ in children aged 4-6 years. This study aims to determine the main factors that affect the failure of toilet training in children aged 4-6 years. This research is a descriptive explorative study, with the population are all parents / trustee who have children aged 4-6 years and which stayed or recorded at RW(citizens association) 05 Pujiharjo Village Tirtoyudo Subdistrict Malang Regency a number of 55 respondents, data collection using interviews method. Result of the research showed that the biggest factor that affect the failure of toilet training was the mistake in teaching toilet training by 94,5%, inappropriate parentingÂ by 91%, unprepared emotional chidren by 61,8%. The result might happen because the way or uncorrect method of toilet training, resulting in children less understand the importance of urinating and defecating in the bathroom, how to do it and do not follow the stages consistenly, so that the child fails in doing toilet training. The research suggestion for health care at Pujiharto Village to provide counseling to parents about toilet training.